2007
DOI: 10.1002/ajh.20859
|View full text |Cite
|
Sign up to set email alerts
|

Monosomy 7 with severe myelodysplasia developing during imatinib treatment of Philadelphia‐positive chronic myeloid leukemia: Two cases with a different outcome

Abstract: Chromosomal abnormalities in Ph‐negative metaphases from patients with chronic myeloid leukemia (CML) treated with imatinib have been described in some cases. Trisomy 8 is the most frequent, but monosomy 7 has also been described. However, the association of these chromosomal alterations with myelodysplasia has been scarcely reported. We report the appearance of monosomy 7 in Ph‐negative cells, associated with severe dysplasia, in two patients with CML treated with imatinib, with a different outcome: one with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 17 publications
2
24
0
Order By: Relevance
“…This suggested that chromosomal abnormality during imatinib therapy may have different clinical implications from those associated with other cytotoxic chemotherapies. Only rare cases showing chromosomal abnormality during imatinib therapy developed MDS/ AML (15)(16)(17)(18). In the revised recommendations of European LeukemiaNet chromosomal abnormality in Ph negative cells at any time is categorized into warning category (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggested that chromosomal abnormality during imatinib therapy may have different clinical implications from those associated with other cytotoxic chemotherapies. Only rare cases showing chromosomal abnormality during imatinib therapy developed MDS/ AML (15)(16)(17)(18). In the revised recommendations of European LeukemiaNet chromosomal abnormality in Ph negative cells at any time is categorized into warning category (19).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical courses in such patients were reported to usually be similar to patients without chromosomal aberration, and some are transient (14). However rare cases with chromosomal abnormality developed myelodysplastic syndrome (MDS) or acute myeloblastic leukemia (AML) (15)(16)(17)(18). We report a CML patient who developed MDS with Ph-negative monosomy 7 chromosome following transient bone marrow dysplasia without chromosomal abnormality during imatinib treatment.…”
Section: Introductionmentioning
confidence: 92%
“…To date, approximately 40 patients with monosomy 7 in Ph-negative cell population as the sole abnormality or in more complex karyotypes, have been reported in CML patients receiving imatinib treatment (5,6,(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Of these 40 patients, 22 displayed monosomy 7 as the sole abnormality in the absence of other clonal changes.…”
Section: Resultsmentioning
confidence: 99%
“…However, tyrosine kinase inhibition fails to eradicate the quiescent Ph-positive hematopoietic stem cells and clinical relapse is a common consequence of ceased therapy (2). Noteworthy, a subset of patients (2-17%) treated with imatinib show clonal cytogenetic changes in the Ph-negative cell population (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). These cytogenetic changes include trisomy 8 and monosomy 7 that are frequently observed in myelodysplastic syndromes (MDS) and acute myeloid leukemia (AML), which has raised concerns about their clinical implications.…”
Section: Introductionmentioning
confidence: 99%
“…A number of these patients have dysplastic features in their bone marrow, and a few patients developed acute myeloid leukemia (AML) [5,7,[12][13][14]. However, the relationship between the development of cytogenetic abnormalities, myelodysplastic syndrome (MDS), or acute leukemia and treatment with imatinib is not clear.…”
Section: Introductionmentioning
confidence: 99%